Neurogenic communication disorders and the life participation approach : the social imperative in supporting individuals and families - Holland, Audrey L.; Elman, Roberta J. (Plural Publishing, 2021)
The Life Participation Approach to Aphasia (LPAA) is an evolutionary change in the way practitioners view aphasia intervention. By focusing on meeting the needs of individuals affected by aphasia, LPAA can produce real, meaningful enhancement to the quality of life. Neurogenic Communication Disorders and the Life Participation Approach: The Social Imperative in Supporting Individuals and Families breaks down the past, present, and future of the LPAA movement with contributions from a range of new and experienced practitioners. In addition, this text provides a roadmap for professionals interested in incorporating person-centered intervention for aphasia and other neurogenic communication disorders, including primary progressive aphasia, dementia, and traumatic brain injury. Within this book, clinicians will find tips, tools, and guidance for integrating a life participation approach into their practice, as well as first-hand descriptions of the positive benefits this approach can have for those living with neurogenic communication disorders.